Microwave Assisted Synthesis of Some Biologically Active Benzothiazolotriazine Derivatives - Prashant Kriplani; Pawan Swarnkar; Rinku Maheshwari; K. G. Ojha (E-Journal of Chemistry)
Synthesis of some biologically active benzothiazolotriazine derivatives by microwave irradiation is reported. 2-Amino-6-substituted benzothiazoles 1 on treatment with benzaldehyde in anhydrous ethanol afforded 2-benzylidenoimino-6-substitutedbenzothiazoles 2 which underwent cyclisation with ammoniumthiocyanate in dioxane to give 2-phenyl benzothiazolo [3,2-α]-s-triazine-4-[3H] thiones 3.These both steps were carried out in microwave. Compound 3 with benzoyl chloride in anhydrous pyridine gave 2-phenyl-3-(benzoyl) benzothiazolo [3,2-α]-s-triazine-4-thiones 4 in good yields. The structure of all these compounds have been supported by their elemental analysis and their spectral data. All synthesized compounds were tested for their antibacterial activity using standard drug.